A new species of Lerista Bell, 1833 (Reptilia: Scincidae) from Cape York Peninsula, Queensland, belonging to the Lerista allanae clade but strongly disjunct from other members of the clade - Amey, Andrew P.; Couper, Patrick J.; Wilmer, Jessica Worthington (Zootaxa, 2019)
A species of the skink genus Lerista is described from Cape York Peninsula in Queensland.  The species is biogeographically interesting as it appears to be separated by at least 500 km from its nearest relatives, members of the Lerista allanae clade.  The role of Pleistocene sea level changes altering availability of suitable habitat for these sand specialists is discussed as a possible driver of isolation and speciation.